(3HOjYjI Uaj GdOjf GdMdis - (3YHO GdYRjR Hf SQGjG Hf Ydj Hf CHj GdbGSe GdSfHSj GdWGFj GdMdj , Uaj GdOjf,J (B750 (3g` s ((3YeQ CfSi Hf eMeO OjH GdUbYGf GdHjQhJi s)
(3ChdgG (B:s
(3Ef LFJ SdYkG aSd Yf LjQg GdYde hGbQi GdSdGe Ydi YQH HPi Sde s
(3BNQgG (B:s
(3aEf SYOJ aeOMi ajc ehLHg hEf TbjJ aPfHi ehLH GdfZe s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B141 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B247 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B582s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B233s
Keywords: (3GdHdGZIs